2019
DOI: 10.17161/kjm.v10i4.8669
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Utilizing Medicaid Smoking Cessation Benefits

Abstract: IntroductionSmoking is the number one preventable cause of death in the United States. Under the Affordable Care Act, Kansas Medicaid covers all seven FDA-approved smoking cessation therapies. However, it is estimated only 3% of Kansas Medicaid smokers use treatment compared to the national estimate of 10%. The objective is to determine systemic barriers in place that prevent optimal utilization of Medicaid smoking cessation benefits among KU Medical Center Internal Medicine patientsMethodsFor this quality imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Lack of awareness is likely an important factor influencing utilization among employees, as only 51% stated their agency offered health insurance benefits for cessation treatment. These findings are consistent with prior studies that have demonstrated low awareness of covered cessation benefits among individuals using tobacco 23,24 . Awareness seemed to be higher among focus-group participants, although several did not know what specific benefits their agency offered and had done little to promote them.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Lack of awareness is likely an important factor influencing utilization among employees, as only 51% stated their agency offered health insurance benefits for cessation treatment. These findings are consistent with prior studies that have demonstrated low awareness of covered cessation benefits among individuals using tobacco 23,24 . Awareness seemed to be higher among focus-group participants, although several did not know what specific benefits their agency offered and had done little to promote them.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are consistent with prior studies that have demonstrated low awareness of covered cessation benefits among individuals using tobacco. 23,24 Awareness seemed to be higher among focus-group participants, although several did not know what specific benefits their agency offered and had done little to promote them.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to include behavioral intervention, such as advice and counseling in a combination of various services for smokers to make it easier to stop smoking. Based on the analysis of previous cessation attempts of the clients and previously published literature, 18 , 20 , 29 it is evident that NRT alone had not worked for many clients in the past. This finding supports existing ‘real‐world’ studies that highlight the importance of combining pharmacotherapies with behavioral support to increase their odds of successful quit attempts.…”
Section: Discussionmentioning
confidence: 99%
“…Many smokers are unaware of and underestimate the benefits of available cessation assistance. 20 , 21 The health system is the most appropriate setting for smoking cessation advice, where the best practice model of care for smoking cessation should be embedded with the provision of brief advice to promote cessation and the facilitation of evidence‐based treatments (Bain et al, 2019). 19…”
Section: Introductionmentioning
confidence: 99%
“…NRT is an over-the-counter product that comes in a wide variety of brands, package sizes, and formulations, but insurance plans may only cover a few of these formulations. 11 In order to fill a prescription, the pharmacist needs to access the patient's insurance information, scan the National Drug Code (NDC) number from the NRT package, and see if the brand and formulation is covered by the patient's insurance. If the pharmacist finds that particular package is not covered, they may check different brands or assume the patient's prescription plan does not cover NRT.…”
Section: Introductionmentioning
confidence: 99%